Sepak Bola Modifikasi Untuk Melatih Interaksi Sosial Anak Autis - afdhol ma'ruf; Pamuji Pamuji; Sri Joeda Andajani (Jurusan Pendidikan Luar Biasa Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2023)
The socializing activities that exist at the Cita Hati Bunda Sidoarjo Foundation are the creation of a social interaction between students and students, students and teachers, students and the surrounding community, the ability to interact socially is also mandatory for autistic students. This study aims to examine social interactions in playing modified soccer for autistic children at the Cita Hati Bunda Sidoarjo Foundation. The research design used a pre-experimental type of one-group pre-test post-test. The number of subjects in this study were 6 autistic students. The average pre-test score was 30.83 and the post-test average was 70.42 with the treatment/intervention 6 times in class. The conclusions of this study are H zero (H0) is rejected and the working hypothesis (Ha) is accepted, Z count (Zh) = 2.096 is greater than Z table (Zt) = 1.96 with a critical value = 5%. So the modified soccer game affects the social interaction of autistic children.